205k views
3 votes
3Select the correct answer.What is the solution of the following equations?y - 4x = 03x + y = 9OA.x = 0, y =OB.T =OC. x = 1, y = -1D. x = 4, y =ResetNext

User Double M
by
5.9k points

1 Answer

2 votes

Given the system of equations:


\begin{gathered} y-4x=0\rightarrow(1) \\ 3x+6y=9\rightarrow(2) \end{gathered}

From equation (1), y = 4x

Substitute with y in the equation (2), then solve for x


\begin{gathered} 3x+6\cdot4x=9 \\ 3x+24x=9 \\ 27x=9 \\ x=(9)/(27) \\ \\ x=(1)/(3) \end{gathered}

So, y = 4x = 4 * 1/3 = 4/3

So, the answer will be option B) x = 1/3 , y = 4/3

User Fasseg
by
6.4k points